A variant of the CXCL11 gene may influence susceptibility to contact allergy, particularly in polysensitized patients - Westphal, Götz Alexander; Schäkel, Knut (Contact dermatitis, 2016)
BACKGROUND: Hereditary factors may influence individual susceptibility to contact allergy. OBJECTIVES: To investigate genetic variants with impacts on early inflammatory reactions and T cell functions that possibly increase the risk of contact allergy. PATIENTS AND METHODS: Three hundred and seventy two patients undergoing patch testing were recruited from the Information Network of Departments of Dermatology (IVDK). Of these, 133 were monosensitized and 239 were polysensitized, defined as reacting to three or more unrelated sensitizers. Within the polysensitized individuals, a subgroup with at least one particularly strong patch test reaction (strong reactors; n = 194) was considered. Three hundred and forty-seven blood bank donors served as controls. Fifteen genetic variants in 13 genes were analysed. RESULTS: The homozygous variant CXCL11 AA genotype (rs6817952) was significantly more frequent among polysensitized patients (10 of 239 = 4.2%; p = 0.0048; odds ratio 7.49; 95%CI: 1.7-36.1) than among monosensitized patients (2.2%) and in the control group (0.6%). None of the remaining genetic variants investigated were characterized by similarly strong associations. However, the significance was lost after correction for multiple comparisons. CONCLUSIONS: The homozygous variant CXCL11 genotype is associated with an increased risk of contact allergy. To confirm this exploratory finding, further independent studies are needed.